From Policy to Practice: Implementation of a Competency-Based Literacy Curriculum in an Islamic Boarding School in the Era of Industrial Revolution 4.0 - Herman Herman (At-Tafkir, 2025)
The development of a competency-based literacy curriculum is a response to the challenges of the 4.0 industrial revolution era. Teachers still believe that the implementation of reading literacy is the responsibility of Indonesian language teachers, while numeracy literacy is the responsibility of mathematics teachers. Theoretically, the development of a competency-based reading and numeracy literacy curriculum is the responsibility of all subject teachers taught at madrasahs. This study aims to describe and analyze the implementation of a competency-based literacy curriculum at the MTsS Nurul Falah Aceh Barat boarding school madrasah. This study uses a qualitative case study approach to examine and analyze in depth and detail the competency-based literacy curriculum. The reason for choosing this qualitative case study method is to strengthen the contextual relevance to the phenomenon being studied. The research subjects consisted of the madrasah principal, vice principal for academic affairs, boarding school leader, and teachers at MTsS Nurul Falah in West Aceh Regency. Data were collected through observation, interviews, and document analysis. The data were then analyzed by transcribing, taking notes, and examining documents to generate ideas, coding the data, developing themes, interpreting information, and drawing conclusions. The results of the study indicate that the curriculum has integrated reading literacy and numeracy, but its implementation is still not optimal, so that students' literacy skills remain low. A literacy-based curriculum has very significant implications for efforts to develop an effective curriculum and for the sustainable development of students' skills. The practical contribution of this study is to help improve the quality of learning practices by providing a range of information related to methods and strategies for implementing a literacy-based curriculum. Meanwhile, the theoretical contribution is to assist in the development of a better and more comprehensive theory of reading literacy and numeracy in an effort to improve understanding and the quality of the application of a literacy competency-based curriculum in the learning process at boarding schools.